Implementasi Strategis Operasional Vessel Traffic Service (VTS) Tanjung Priok untuk Peningkatan Keselamatan Pelayaran - Hijrah Khaqo; I Dewa Ketut Widana; Sri Yanti Yosepha (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
Vessel Traffic Services (VTS) play a vital role in enhancing navigation safety and improving the efficiency of maritime transportation. However, the high density of vessel traffic and the occurrence of maritime incidents within the Tanjung Priok VTS service area indicate the need for continuous evaluation of its operational effectiveness. This study aims to analyze the role of Tanjung Priok VTS in supporting navigation safety and to formulate appropriate development strategies. It addresses the research gap by providing a SWOT-based strategic analysis of VTS operations at Indonesia’s busiest port in terms of vessel traffic density. A qualitative case study approach was employed. Data were collected through in-depth interviews, direct observation, and document analysis involving the Manager, Supervisors, and Operators of Tanjung Priok VTS. The data were analyzed descriptively and supported by SWOT analysis to identify the organization's internal and external factors. The findings indicate that Tanjung Priok VTS plays a significant role in supporting navigation safety through vessel traffic monitoring, navigational information services, and traffic organization. Human resource competence, monitoring technology, and standardized operating procedures were identified as the main strengths, whereas limited real-time data integration and increasing operator workload remain key challenges. The study concludes that strengthening personnel competence, modernizing technology, integrating information systems, and enhancing inter-agency coordination are essential strategies for improving VTS effectiveness and supporting sustainable navigation safety in Indonesia.